1975
DOI: 10.3758/bf03203301
|View full text |Cite
|
Sign up to set email alerts
|

Foreground and background in dynamic spatial orientation

Abstract: The dependency of visually induced self-motion sensation upon the density of moving contrasts as well as upon additional stationary contrasts in the foreground or background was investigated. Using two different optokinetic stimuli, a disk rotating in the frontoparallel plane, and the projection of horizontally moving stripes onto a cylindrical screen, it was found that: (1) visually induced self-motion depends upon the density of moving contrasts randomly distributed within the visual field and, with a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
78
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(91 citation statements)
references
References 12 publications
10
78
1
Order By: Relevance
“…The order of surfaces in d~th may 1)e given by texture occlusion and disocclusion, motion perspective, stereopsis, and so on. Consistent with this notion is the evidence that both vection and postural adjustments are driven by motion of surfaces perceived to be in the background, but not by motion of surfaces perceived to be in the foreground (Brandt, Wist, & Dichgans, 1975;Ohmi, Howard, & Landolt, 1987).…”
supporting
confidence: 68%
“…The order of surfaces in d~th may 1)e given by texture occlusion and disocclusion, motion perspective, stereopsis, and so on. Consistent with this notion is the evidence that both vection and postural adjustments are driven by motion of surfaces perceived to be in the background, but not by motion of surfaces perceived to be in the foreground (Brandt, Wist, & Dichgans, 1975;Ohmi, Howard, & Landolt, 1987).…”
supporting
confidence: 68%
“…In this study, the dependent variable consisted of the duration of these three stages, i.e., the time to onset of CV, the time from onset to saturation or full vection, and the duration of the aftereffect. These durations were measured since they most probably represent the best indica-'tors of the effectiveness of a given CV stimulus (Brandt, Wist, & Dichgans, 1975;Dichgans & Brandt, 1978). The procedure was repeated at least twice with right and left rotation of the drum for each luminance level.…”
Section: Apparatusmentioning
confidence: 99%
“…Until recently, it has been thought that the peripheral visual field played a dominant role in self-motion perception, and the central visual field played little or no role [2,23]. Brandt et al [2] reported that circular vection could be induced when 30°displays were presented in the periphery but not when they were presented in the central visual field.…”
Section: Stimulus Effect Of Doks In Inducing Vectionmentioning
confidence: 99%
“…Brandt et al [2] reported that circular vection could be induced even when large parts of the central field were masked (up to 120°) [9]. On the other hand, Paulus et al [19] concluded that the foveal region has a powerful contribution.…”
mentioning
confidence: 99%